Feed‐induced Variation in the Carotenoid Composition of Brine Shrimp. Issue 3 (5th June 2020) - Huang, Jin; Hui, Bodi
Abstract : Brine shrimp is a genus of aquatic crustacean, and is considered a dietary carotenoid resource by local residents from eastern China. In the present study, harvested brine shrimp were fed with the dried powders of tomato fruit ( Solanum lycopersicum, as a lycopene source), marigold flower ( Tagetes erecta L., as a lutein ester source), halophile green algae ( Dunaliella salina, as free lutein and β ‐carotene sources) and freshwater green algae ( Haematococcus pluvialis, as an astaxanthin ester source). After 30 min of free feeding, the total carotenoid amount and CC of brine shrimp were assessed by UV–VIS and C18‐HPLC (high performance liquid chromatography) every hour, respectively. Data from those investigations suggested that: (1) Both carotenes and xanthophylls from feeds were able to be accumulated in brine shrimp. (2) Hydrolysis took place with lutein and astaxanthin esters to form their free forms, (3) β ‐Carotene was converted into a keto‐carotenoid, canthaxanthin. Those observations confirmed that a number of carotenoid molecular modifications had taken place in vivo . Although it was observed that a significant amount of carotenoids were lost during their accumulations in vivo, brine shrimp would still be considered as a species of bio‐encapsulated free carotenoid carrier, and therefore as a possible dietary carotenoid resource.